Adaptive increases in liver cocaine n-demethylation induced by the drug in rats receiving different levels of utilizable protein. I. Its relationship with the protein efficiency - Ramos Aliaga, R. (1981)
Adaptive increases in liver cocaine n-demethylation induced by the drug in rats receiving different levels of utilizable protein. I. Its relationship with the protein efficiency